Socialization of the quality of school graduates to increase society participation in achieving high-quality education - Ida Martinelli; Nalil Khairiah; Nurhasanah Nasution; Leylia Khairani (Universitas Muhammadiyah Magelang, 2021)
Graduating is not only about taking compulsory education, but also fulfilling the qualifications of graduates' abilities which include attitudes, knowledge, and skills. This is in accordance with the provisions of the education system contained in Government Regulation 32 of 2013. The lack of understanding of graduate quality standards is due to minimal socialization carried out by the government and related institutions. Therefore, this community service is important in order to provide knowledge to the society, so that it can further increase its participation to help in realizing high-quality education. The implementation model is carried out through the partnership method, by involving the government of Pematang Johar Village in several stages, namely: 1) pretest; 2) socialization; and 3) posttest to measure the success rate of the program. The results show that there is an increase in knowledge for the society about the quality of graduates in accordance with national education standards and there is a better awareness that society participation is needed to help realize high-quality education.